2018
DOI: 10.1111/dme.13854
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of observational studies of the association between pioglitazone use and bladder cancer

Abstract: Aim To conduct a systematic review of all observational studies on the effect of pioglitazone on the risk of bladder cancer.Methods The MEDLINE and EMBASE databases were queried for papers published between 1 January 2000 and 30 October 2017. We took into consideration observational studies (both retrospective and prospective) that included participants with Type 2 diabetes prescribed anti-hyperglycaemic drugs.Results While some studies reported an association, others did not, and meta-analyses of these studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…In line with previous reports, the current data also showed a lower incidence of MI in pioglitazone users [57]. Although the potential risks of HF and bladder cancer in pioglitazone users have gained clinical attention [58,59], the issue of increasing risks of bladder cancer remains unconfirmed due to the conflicting results from previous studies [58][59][60]. In the present study, using the real-world data in Taiwan, the increased risk of newly diagnosed bladder cancer in the pioglitazone group was substantial by 34% (HR = 1.34) but not statistically significant due to the limited sample size.…”
Section: Discussionsupporting
confidence: 85%
“…In line with previous reports, the current data also showed a lower incidence of MI in pioglitazone users [57]. Although the potential risks of HF and bladder cancer in pioglitazone users have gained clinical attention [58,59], the issue of increasing risks of bladder cancer remains unconfirmed due to the conflicting results from previous studies [58][59][60]. In the present study, using the real-world data in Taiwan, the increased risk of newly diagnosed bladder cancer in the pioglitazone group was substantial by 34% (HR = 1.34) but not statistically significant due to the limited sample size.…”
Section: Discussionsupporting
confidence: 85%
“…We were disappointed to see in the recent article by Ripamonti et al ., published in Diabetic Medicine , that there still are people pursuing a connection between pioglitazone and bladder cancer, despite all of the accumulated evidence that this association is a red herring . The possibility of a connection first came about during pre‐clinical studies because of an association between pioglitazone and bladder cancer in male, but not female, rats; no such association was observed in other animals .…”
Section: Bladder Cancer Appearing During the First Year Of The Proactmentioning
confidence: 99%
“…We do not feel that it is appropriate, as suggested by Ripamonti et al . , to devote further resources to yet more research into a connection between pioglitazone and bladder cancer. Rather, randomized controlled trials should be undertaken to establish whether combining pioglitazone with sodium‐glucose co‐transporter‐2 inhibitors or with glucagon‐like peptide‐1 receptor agonists, or combining sodium‐glucose co‐transporter‐2 inhibitors with glucagon‐like peptide‐1 receptor agonists, leads to increased reduction in cardiovascular events, and whether triple therapy with these agents would reduce such outcomes even more .…”
Section: Bladder Cancer Appearing During the First Year Of The Proactmentioning
confidence: 99%
“…insulin infusion. In their Letter to the Editor [1], the authors asserted that biased and inconsistent studies were included in a metaanalysis by Ripamonti et al [2] Let us clarify that in the cited paper [2] we showed heterogeneity measures, but no pooled estimate has been calculated for any effect measure, exactly for the reason that included studies were, for different reasons, biased or poorly conducted. IIn the light of this premise, our systematic review showed how no conclusion on the association between pioglitazone and bladder cancer can be posited, as most studies in this area are affected by different sources of bias, most notably time-related biases.…”
mentioning
confidence: 91%